KEEFEKTIFAN MEDIA PEMBELAJARAN BERBASIS STEAM-LIFE SKILLS UNTUK MENINGKATKAN LIFE SKILLS SISWA KELAS III SDN REJOSARI 01 SEMARANG - Marisa Salsabilla; Veryliana Purnamasari; Arfilia Wijayanti (STKIP Subang, 2023)
The background that prompted this research was that learning media based on STEAM life skills had never been applied. In addition, there is a lack of social skills in students, such as the ability to cooperate and participate, the ability to communicate orally. Students also do not fully have awareness of their own potential and encouragement to develop it during learning, and there is no awareness from students to be skilled in terms of skills in creating or making products. The goal to be achieved in this research is to determine the effectiveness of learning media based on STEAM life skills. This type of research is descriptive quantitative research. The results of the research on the effectiveness of learning media based on STEAM life skills to improve the life skills of SDN Rejosari 01 Semarang students in the experimental class after being treated with a total of 28 students got an average of 137.54 and in the control class with a total of 27 students got an average of 82.93. Meanwhile, based on the paired sample t test, it is known that sig. (2-tailed) before being given treatment and after being given treatment in the experimental class of 0.000 < 0.05 so it can be concluded that there are differences before and after treatment of students' life skills. While the sig. (2-tailed) before being given treatment and after being given treatment in the control class of 0.314 > 0.05 so it can be concluded that there is no difference before and after treatment of students' life skills. Meanwhile, student responses to learning media based on STEAM life skills obtained from the results of the questionnaire obtained an average percentage of 81.36%, this result was included in the very easy category. So it can be concluded that learning media based on STEAM life skills is effective for improving the life skills of class III students at SDN Rejosari 01 Semarang.